(untitled) (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2026)
The development of information technology has encouraged the digitalization of notarial services through the concept of cyber notary, including the use of electronic documents and electronic signatures in the execution of authentic deeds. Although electronic documents and electronic signatures have received legal recognition, their application to authentic deeds continues to raise issues concerning validity, legal certainty, and evidentiary strength. This study aims to analyze the validity of electronically signed authentic deeds, the legal certainty of their application, and their evidentiary strength within the Indonesian legal system. This study employs a normative juridical method using a statutory approach, conceptual approach, and case approach. Legal materials were analyzed using qualitative-prescriptive analysis through a literature study of relevant legislation, court decisions, and legal literature. The results show that the validity of an electronic signature does not automatically establish a document as an authentic deed, as its authenticity remains dependent on the authority of the notary and the fulfillment of the formal and substantive requirements for the execution of an authentic deed. The implementation of cyber notary also continues to face challenges concerning the harmonization of notarial law and electronic transaction regulations, particularly regarding the presence of the parties, reading of the deed, signing procedures, and evidentiary strength. Therefore, a comprehensive legal framework integrating the validity of electronic signatures, legal certainty, and evidentiary strength is required to ensure that the digitalization of notarial services continues to provide legal certainty and protection for the parties.